2014
DOI: 10.1093/jac/dku222
|View full text |Cite
|
Sign up to set email alerts
|

Micafungin is more active against Candida albicans biofilms with high metabolic activity

Abstract: Our study suggests that the metabolic activity of biofilm may have a role in future evaluations of micafungin for the eradication of C. albicans biofilms (e.g. the lock therapy approach).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Notably, micafungin is more active against biofilms with high metabolic activity at least in case of C. albicans (Marcos‐Zambrano et al . ). Furthermore, enhanced micafungin activity was observed against C. parapsilosis biofilm earlier by Shirazi and Kontoyiannis ().…”
Section: Discussionmentioning
confidence: 97%
“…Notably, micafungin is more active against biofilms with high metabolic activity at least in case of C. albicans (Marcos‐Zambrano et al . ). Furthermore, enhanced micafungin activity was observed against C. parapsilosis biofilm earlier by Shirazi and Kontoyiannis ().…”
Section: Discussionmentioning
confidence: 97%
“…The XTT colorimetric tetrazolium assay was used to evaluate the effects of laser treatments on total metabolic activity of C. albicans biofilm [ 23 , 24 ]. A commercial kit (AppliChem GmbH, Darmstadt, Germany) was employed following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Time-lapse recordings of yeast cell cultures under these experimental conditions showed that when budding cells started to grow, they blow up probably as a consequence of the loss of cell wall integrity, caused by their inability to synthetize new fungal wall ␤-glucan (data not shown). The MF effect depends on the metabolic status of the cells, since the biosynthesis of different structural components for the cell wall requires energy, which is partially obtained from mitochondrial activity (20). Thus, yeasts grown in a medium rich in nutrients with an active metabolism were sensitive to the echinocandin effect, in contrast to cells grown in YNB (Fig.…”
Section: Discussionmentioning
confidence: 99%